The Impact of Non-Violent Muslim Extremism: Reflections on Indonesia and Malaysia - Saat, Norshahril (Muslim Politics Review, 2023)
Numerous pieces of research have addressed the issue of terrorism and radicalism in Southeast Asia, and security studies are inundated with works covering its origin, function, and impact. However, this article argues that equal attention should be given to non-violent extremism and its impact on societies at the discursive level. By examining case studies from Indonesia and Malaysia, two Muslim-majority nations, this article contends that the question is not whether non-violent extremism directly or indirectly leads to terrorism, but how it can also shape policies and regulations through lobbying, trigger mass political mobilization, and nurture intolerance and hatred towards minority groups.